Effect of calcium and magnesium nutrition on vegetative growth and tuber yield of potato (Solanum tuberosum) - Navdeep Singh; Rishu Sharma; Deepak Kumar; Jyoti Verma (Environment Conservation Journal, 2024)
A field experiment was conducted to investigate the effect of calcium nitrate and magnesium sulfate on the growth and tuber yield in potato (Solanum tuberosum L). Experiment was carried out in split-plot design comprising of nine calcium nitrate and magnesium sulfate treatments i.e.T1- Ca(NO3)2 @ 0.5%, T2- Ca(NO3)2 @ 1%, T3- Ca(NO3)2 @ 2%, T4- MgSO4 @ 0.5%, T5- MgSO4 @ 1%, T6- MgSO4 @ 2%, T7- Ca(NO3)2 @ 1% + MgSO4 @ 1%, T8- Ca(NO3)2 @ 2% + MgSO4 @ 2%, T9- Control on two potato varieties i.e. Kufri Jyoti and Kufri Chandramukhi. Data collected on different parameters were analyzed using CPCS1 software. Among all the calcium nitrate and magnesium sulfate treatments, application of Ca(NO3)2 @ 2% + MgSO4 @ 2% was found to be the best for most of the parameters studied and between the varieties Kufri Jyoti was found highly significant for the different parameters under study. Hence it can be concluded that commercial cultivation of potato in the central region of Punjab can be successfully supplemented with application of Ca (NO3)2 + MgSO4 and variety Kufri Jyoti.